Building Landmarks, Smoothing Out Markets : An Enhanced Competition Framework in Romania - Aprahamian, Arabela; Pop, Georgiana (Washington, DC: World Bank, 2015)
Romania identified competition as key to its effective economic development and is positioning the Competition Council to become more visible and effective. Improving Romania’s competitive environment will attract new firms, weed out inefficient ones, and enhance growth potential. An effective competition policy leads to success in the areas of Romania's domestic market efficiency, economic growth and European market integration. Following a comprehensive functional review of the Romanian Competition Council carried out by the World Bank in 2010, weaknesses, needs and priorities were identified. This book presents the results of the World Bank’s Advisory Services which were designed to provide solutions in the identified reform areas during 2012-2015.